Withania somnifera (L.) Dunal as Add-On Therapy for COPD Patients: A Randomized, Placebo-Controlled, Double-Blind Study - Singh, Priyam; Salman, Khushtar Anwar; Shameem, Mohammad; Warsi, Mohd Sharib (Frontiers in Pharmacology, 2022)
Background: The current gold-standard therapies for chronic obstructive pulmonary disease (COPD) lack disease-modifying potential and exert adverse side effects. Moreover, COPD patients are at a higher risk of severe outcomes if they get infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, the cause of the current epidemic. This is the first study to document clinical research on an adaptogenic and steroidal activity–containing herb as a complementary medicine for COPD treatment. Objective: We aimed to evaluate the efficacy of Withania somnifera (L.) Dunal [Solanaceae] (WS) as an add-on therapy for COPD patients. Methods: A randomized, placebo-controlled, and double-blind clinical study was conducted. A total of 150 patients were randomly assigned to three groups: control, placebo, and WS group. In addition to conventional medicines, WS root capsules or starch capsules were given twice a day to the WS group and the placebo group, respectively. Their lung functioning, quality of life, exercise tolerance, systemic oxidative stress (OS), and systemic inflammation were assessed before and after 12 weeks of intervention. WS root phytochemicals were identified by LC-ESI-MS. The inhibitory activity of these phytochemicals against angiotensin-converting enzyme 2 (ACE-2); the SARS-CoV-2 receptor; myeloperoxidase (MPO); and interleukin-6 (IL-6) was evaluated by in silico docking to investigate the mechanism of action of WS. Results: The pulmonary functioning, quality of life, and exercise tolerance improved, and inflammation reduced notably the most in the WS group. Systemic oxidative stress subsided significantly only in the WS group. Although a minor placebo effect was observed in the SGRQ test, but it was not present in other tests. Withanolides found in the WS roots demonstrated substantial inhibitory activity against the proteins ACE-2, MPO, and IL-6, compared to that of a standard drug or known inhibitor. Moreover, FEV1% predicted had significant correlation with systemic antioxidative status (positive correlation) and malondialdehyde (MDA, negative correlation), suggesting that the antioxidative potential of WS has significant contribution to improving lung functioning. Conclusion: Our study clinically demonstrated that WS root when given along with conventional drugs ameliorated COPD significantly more in comparison to the conventional drugs alone, in GOLD 2 and 3 categories of COPD patients. In silico, it has potent inhibitory activity against SARS-CoV-2 receptor, ACE-2, MPO, and IL-6.